EMPOWERMENT AND FORMATION OF MATERNAL AND CHILD HEALTH CADRES FOR DELIVERY PLANNING AND PREPAREDNESS IN THE FACE OF OBSTETRIC AND NEONATAL COMPLICATIONS IN BOJONEGORO, INDONESIA - Handayani, Aris (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
In Bojonegoro, the maternal mortality rate has tended to increase over the last 2 years, in 2017 there were 17 people distributed at 100.93 per 100,000 live births in 12 health centres.2017 as many as 17 people spread 100.93 per 100,000 live births in 12 health centres. While in 2018 reached 27 people 157.23 per 100,000 live births. To accelerate the reduction of MMR in Indonesia, the government has issued various policies, such as the planning of childbirth and prevention of complications with stickers (P4K) programme. The programme, which was issued by the Minister of Health in 2007, is a breakthrough effort in accelerating the reduction of maternal and newborn mortality through activities to improve access and quality of services, which at the same time is an activity that builds community potential, especially community awareness for preparation and follow-up in saving mothers and newborns. So that the Bojonegoro Midwifery D III Study Program carries out activities to empower and form maternal and child health cadres in the context of delivery planning and preparedness in the face of Obstetric and Neonatal Complications in Bendo Village, Kapas District, Bojonegoro. The purpose of this community service is to carry out empowerment activities and the formation of maternal and child health cadres in the context of planning childbirth and preparedness in the face of obstetric and neonatal complications in the village of Bendo Kec. Kapas Kab.Bojonegoro.The form of activities is the formation and training of maternal and child health cadres in the context of planning childbirth and preparedness in the face of obstetric and neonatal complications. The source of costs in this activity is charged to funds from DIPA Poltekkes Kemenkes Surabaya. The outputs of this activity are: 1) the formation of maternal and child health cadres who have completed the training; 2) Increased knowledge and skills of Communication, Information, and Education (IEC) of maternal and child health cadres; 2) Maternal and child health cadres disseminate the ability of childbirth planning and preparedness in the face of obstetric and neonatal complications and to carry out counseling on the prevention of complications to pregnant women, fertile women and couples of childbearing age around their place of residence on an ongoing basis; 4) Decreased incidence of maternal mortality.